(untitled) (Global Journal of Medical Research, 2020)
The interaction between the mind and skin diseases has been the focus of study of many researchers around the world; Psychodermatology is the result of the fusion of medical specialties: psychology, psychiatry and dermatology. Dermatologists are aware of the potential for significant improvement of dermatological pathology when addressing the psychological-psychiatric dimension and vice versa, the bidirectional relationship has already been described, we know that it is necessary to break this cycle, but we still have to define the treatment, for which we must know the different therapies.